Pharmacological induction of selective endoplasmic reticulum retention as a strategy for cancer therapy - Mohamed Mahameed (Nature Portfolio, 2020)
Inhibition of PERK, an endoplasmic reticulum (ER) unfolded protein response (UPR) protein, is a potential pharmacological target for cancer treatment. Here, the authors show that inhibition of PERK under ER stress affects trafficking from the ER to the surface of several key receptor tyrosine kinases, suggesting a selective ER retention.